Evaluation Zero Runoff Concept in High-Rise Buildings - Abadan, Achmad Chakim; Kurniyaningrum, Endah; Rinanti, Astri; Pontan, Darmawan (Pandawan Sejahtera Indonesia, 2024)
The increasing need for land in urban areas has led to a reduction in green open spaces, limiting water infiltration and increasing surface runoff. Office areas in South Jakarta currently under construction exacerbate these issues due to limited green land. This study evaluates the application of the zero runoff concept by analyzing two key aspects: surface runoff and building wall contributions. Hydrological simulations were conducted to assess planned flood conditions at outlets before and after the construction of tall buildings (offices), with water management strategies involving infiltration wells, infiltration ponds, rainwater reservoirs, and detention reservoirs. Two scenarios were analyzed: the first based on the 95th percentile rainfall volume and the second on flood contribution volumes. Each scenario considered three water runoff management systems: normal outlets, orifice outlets, and pump-assisted drainage. The results show that under the 95th percentile volume, the zero runoff concept is achievable with a capacity exceeding 100% for both scenarios. However, when accounting for flood contributions, only surface runoff with normal outlet conditions meets the zero runoff criteria, achieving a capacity of 112%. Simulations using three models: 1A, 2A, and 3A, demonstrate that pre-construction conditions, characterized by green open spaces with dense vegetation, significantly influence runoff management. These findings emphasize the importance of eco-drainage strategies, such as infiltration wells and retention ponds, in mitigating urban runoff and achieving sustainable water management in high-density areas.